Aplicação da metodologia da problematização com o Arco de Maguerez para a aprendizagem significativa de química - Kimura, Rorigo Kendi (2020)
One of the main characteristics of the Problematization Methodology with the use of Arc of Maguerez is the motivational factor, where the learner seeks knowledge to find a solution to a problem present in reality, and during this process there is an occurrence of learning. The motivational factor characteristic of this methodology may favor a predisposition to learn, which is one of the necessary requirements for meaningful learning. Therefore, a question arose to the development of this research: Can the use of the Problematization Methodology with the use of Arc of Maguerez contribute to meaningful learning? To answer this question, this work was developed with the general objective of investigating the contribution of the Problematization Methodology with the use of the Arc of Maguerez for a meaningful learning in the Teaching of Chemistry. To this end, a applied qualitative research was carried out with 26 students of the second semester of graduation in chemistry during a discipline of the Laboratory of Inorganic Chemistry, in the east side of the capital of São Paulo, where the students had as an initial problem a mixture of four substances that can be separated using general mixture separation processes. The search for evidence of meaningful learning took place by evaluating the acquisition of concepts, their use in related areas and knowledge retention. The results obtained reveal that there was a acquisition knowledge in a meaningful way, as part of the students were able to use the acquired knowledge in a problematic situation different from the one presented initially, in addition to presenting knowledge retention, configuring that there were changes in the subsumer.